1984
DOI: 10.1007/bf01952405
|View full text |Cite
|
Sign up to set email alerts
|

Somatomedin-C in zinc deficiency

Abstract: A significant decrease in the activity of somatomedin-C (SM-C) was observed due to zinc deficiency. SM-C activity correlated significantly with b.wt gain and with the status of zinc in rats. The present findings provide an insight into the mechanism by which zinc promotes growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 12 publications
3
14
2
Order By: Relevance
“…However, the authors failed to use a pair-fed group sa it is difficult to attribute the fall in somatomedin A activity entirely to a lack of zinc. Cossack (1984) demanstrated that bath decreased zinc and decreased food intake contribute to the fall in Sm-Co Zinc deficient rats had significantIy depressed growth (as measured by body weight gain) and plasma Sm-C compared to bath pair-fed groups and the ad libitum control group. As weIl, values for f the pair-fed groups were also significantly lower than the AQ libitum controls indicating an effect of decreased food intake alone.…”
Section: Pituitarymentioning
confidence: 87%
See 3 more Smart Citations
“…However, the authors failed to use a pair-fed group sa it is difficult to attribute the fall in somatomedin A activity entirely to a lack of zinc. Cossack (1984) demanstrated that bath decreased zinc and decreased food intake contribute to the fall in Sm-Co Zinc deficient rats had significantIy depressed growth (as measured by body weight gain) and plasma Sm-C compared to bath pair-fed groups and the ad libitum control group. As weIl, values for f the pair-fed groups were also significantly lower than the AQ libitum controls indicating an effect of decreased food intake alone.…”
Section: Pituitarymentioning
confidence: 87%
“…Fasting causes reductions in plasma IGF-I which return to normal with refeedinq (Isiey et al, 1983;1984 Donahue and Phillips, 1989). Thus, it may be a useful tooi for monitoring short-term changes in nutritional status.…”
Section: Pituitarymentioning
confidence: 99%
See 2 more Smart Citations
“…This assumption is supported by the absence of a signi®cant relationship between IGF-1 and s-zinc. Besides growth hormone, dietary zinc and protein are two of the main determinants of IGF-1 synthesis (Thissen et al, 1994), which is shown by experimental and human studies of de®cient and supplemented subjects (Branda AEo-Neto et al, 1995;Ninh et al, 1996;Cossack, 1984). No relationship is found between s-zinc and IGF-1 in children with delayed growth (Mokni et al, 1993), con®rming that the growth-stimulating effect of zinc is only partially mediated by IGF-1; alternatively zinc regulation of IGF-1 may occur at tissue or at cellular level (Branda AEo-Neto et al, 1995); on the other hand IGF-1 levels were positively associated with weight gain but not with linear growth, which could relate to its link with obesity (Gourmelen et al, 1994).…”
Section: Discussionmentioning
confidence: 98%